Respuesta :

Answer:

[tex] \frac{ - (5.8 - 3(3.2))}{ {( - .2)}^{2} } + 3 \\ = \frac{ - (5.8 - 9.6)}{.04} + 3 \\ = \frac{ - ( - 3.8)}{.04} + 3 \\ = \frac{3.8}{.04} + 3 \\ = 95 + 3 \\ = 98 \\ thank \: you[/tex]

Answer:

Below

Step-by-step explanation:

First we will evaluate the brackets (BEDMAS)

      - (5.8 - 9.6) / (-0.2)^2 + 3

      - ( -3.8 ) / ( 0.04) + 3

Because there is a negative sign on both the outside and inside of a bracket, that number becomes positive

      ( 3.8 ) / ( 0.04 ) + 3

Calculate this :

      = 95 + 3

      = 98

Hope this helps! Best of luck <3